Environmental Judge Certification in an Effort to Realize the Green Legislation Concept in Indonesia - Shanty Saleh, Indah Nur; Spaltani, Bita Gadsia (Muhammadiyah University Press, 2021)
The purpose of this research is to find out, analyze, and explain the certification of environmental judges in an effort to realize the concept of green legislation in Indonesia. This research is a normative or doctrinal legal research. The data analysis was carried out qualitatively, so it is hoped that the discussion can accurately answer the problem formulation. This research resulted in the following conclusions: first; Environmental judge certification is important in the effort to implement green legislation in Indonesia based on four considerations, namely: in the context of realizing the 1945 Indonesian Constitution as a green constitution, the strategic role of judges’ decisions in realizing human and environmental justice, contributing to the effectiveness of environmental law enforcement. as well as for the integrated exercise of judicial or judicial powers in the principles of trias politica. Second, that with regard to the application of environmental judge certification in an effort to realize green legislation, the government has issued the RI KMA Decree Number: 134/KMA/SK/IX/2011 which regulates Certification of Environmental Judges which is used as a reference point for legal development regarding the judge certification system. environment in the settlement of civil, criminal and state administration cases in the environmental field. At the same time, judges training and coaching are conducted every year so that the need for the number of certified environmental judges is met in each region. Third, that the direction of legal reform relating to the provisions of environmental judge certification in an effort to realize green legislation can be carried out through guarding the environmental judge certification policy by cooperating with various parties; increase the capability of judges in the field of environmental science; as well as strengthening the judges’ thinking paradigm so that it is pro-environment or pro-natura (green thinking) as a form of embodiment of environmental legal norms according to the green constitution and green legislation in Indonesia. The benefit of this research is in the context of gaining insight among legal experts and legislative parties in improving the substance of law, especially environmental law which represents the concept of green legislation. This research contains novelty and differences from other research in terms of discouraging ideas and models of public policy reform with the concept of green legislation which is used as a legal umbrella in the form of laws on legal substances related to environmental judge certification.